Symbolism and Expression of Performing Panata in the Philippines: An Ethnohistorical Analysis of Nuestro Padre Jesus Nazareno of Quiapo - Mark Inigo Macam Tallara (Religions, 2022)
This paper is about Catholicism in the Philippines, highlighting the events and objects of the popular devotion to the Black Christ Nazarene of Manila, popularly known as Nuestro Padre Jesus Nazareno of Quiapo or NPJN. What are the motivations of the devotees? How have the religious practices changed over time in Quiapo? This study also calls for more scholarly attention to the historical and religious connection between the Philippines and Mexico, so that through them we can better understand how Filipinos reimagined Baroque Catholicism. In addition to commercial goods, the Manila Galleon facilitated the first transpacific people-to-people exchange along with their ideas, and the transmission and transplantation of Catholicism to the Philippines. This study is both historical and ethnographic, using sources from the archives and research materials collected in the Philippines, Mexico, and Spain. Although the devotion to NPJN is central to the arguments of this paper, the discussion takes a broader consideration of Quiapo, a district of Manila as a shared space for performing the sacred vow or PSV, popularly known as panata. This analytical step is consistent with the main argument of this study, that consideration of the PSV particular to Jesus Christ is crucial to understanding the historical and religious connections and how popular Catholicism has changed in the Philippines.